Pembelajaran Berbasis Proyek (PjBL) untuk Mengembangkan Kemampuan Berpikir Kritis Mahasiswa PGMI IAIN Ponorogo - Mukhlison Effendi (IAIN Ponorogo, 2017)
This study is aimed at (1) seeking the light on the application of PjBL to improve critical thinking skills; (2) investigating the factors that influence PJBL's success in improving critical thinking skills; and (3) knowing the students’ responses to the application of PjBL which can improve critical thinking skills. The design used in this research was a qualitative case study. The result of the research was in the form of description and analysis of PjBL usage in improving students' critical thinking skills in Mathematics Study unit at PGMI Department-FATIK, IAIN Ponorogo. Data were gained by using observation techniques, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusions. Validation of triangulation of data sources and methods was conducted. The results showed that the implementation of PjBL in improving critical thinking skills consisted of 3 stages: a) Planning the instructions using RPS; b) Implementing the actions into two face-to-face meeting periods in the classroom and out-of-classroom consultation process through online mode via WhatsApp and offline with face-to-face on out-of-school hours.يهدف هذا البحث إلى: 1) معرفة تطبيق PjBL الذي به يمكن ترقية قدرة الطلاب على التفكير النقدي، 2) معرفة العوامل المؤثّرة لنجاح PjBL في ترقية القدرة على التفكير النقدي، 3) معرفة استجابة الطلاب على تطبيق PjBL الذي يستطيع أن يرقّي القدرة على التفكير النقدي. اتبع هذا البحث المدخل الكيفي بنوع دراسة حالة. ونتيجة البحث في صورة العرض وتحليل اسخدام PjBL في ترقية قدرة الطلاب على التفكير النقدي في مادة تعليم الرياضيّات في قسم التربية لإعداد مدرسي المدارس الإبتدائية، كلية التربية والعلوم التعليمية بالجامعة الإسلامية الحكومية فونوروجو. وبيانات هذا البحث تُجمع بطرق الملاحظة والمقابلة الشخصية والوثائق المكتوبة. أما تحليلها فبطريقة تخفيض البيانات ثم عرضها ويليه الاستنتاج من البيانات. أما التحقق من صحة البيانات فبطريقة المنهج التثليثي في المصادر والطرق. دلّت نتائج البحث على أن تطبيق PjBL في ترقية القدرة على التفكير النقدي يتكوّن من ثلاث مراحل : 1) إعداد التعليم في شكل خطط التعليم، 2) تطبيق التعليم مرّتين في غرفة الدراسة وعملية الاستشارة خارج غرفة الدراسة عن طريق أونلين باستخدام مرفق الوتساب وعن طريق عاديّ بالمقابلة خارج حصة الدراسة.